If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(-16) + -1x = 13 Multiply -1 * -16 16 + -1x = 13 Solving 16 + -1x = 13 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-16' to each side of the equation. 16 + -16 + -1x = 13 + -16 Combine like terms: 16 + -16 = 0 0 + -1x = 13 + -16 -1x = 13 + -16 Combine like terms: 13 + -16 = -3 -1x = -3 Divide each side by '-1'. x = 3 Simplifying x = 3
| 2(a-2)=a+5 | | 2.2x-5=2.8x+6 | | 3(s-10)=24 | | 8x^2+56=0 | | 15-11x=108 | | 45n^2+10=0 | | 45n^2+10=0 | | 9m+10(-14m)=-5 | | .5(3x-2)=5 | | 8+2x-16+x=-15 | | 95=5x^2 | | 2z-3-8z+1= | | x^2+3xy+2y^2-x+2y+2=0 | | -4x-10-1x=25 | | 2x^2-20=0 | | 5X+2=Y | | 14s^2-21s=0 | | 2x-6+8=14 | | 5[1-8x]=5-8x | | .125(w-7)=5 | | 12x^2+5x-7=0 | | 0.222222222x-0.333333333=1 | | .25(d-5)=1 | | 18y-2x=26 | | pb+j=s | | -14.2=-7.1t | | -10x+6=(-7)+(-9) | | .3333(m+6)=4 | | 6x+2-3=14 | | 6n+1-n+5n= | | 3(y-5)=3 | | 1x+2+3x+4=-30 |